Descriptive Study: Distribution of Age, Education, and Occupation of Postpartum Mother’s with Baby Blues - Siti Istiana; Ayu Stefani Yuliana Putri (Jurnal Kebidanan, 2025)
The postpartum period is a critical transition period for the mother, baby and family both psychologically, emotionally, and socially. During psychological adaptation, a women will adjust to her role as parent (mother). Changes during the postpartum period can contribute to happiness but can also cause emotional stress. This period can be a risk factor for triggering complications baby blues. Based on BKKBN data in 2024, as many as 57% of mothers in indonesia experienced symptoms baby blues, namely mild depression after childbirth. This percentage makes indonesia a country with a high risk of baby blues the highest in asia. This research method is descriptive research with a sample of 40 respondents. The results of the distribution based on age are 38 respondents age 20-35 years (95%), the number og multiparous parity is 21 people (52,5%). Distribution based on education there are 18 postpartum mothers who are high school graduates (45%). Distribution based occupation there are 21 respondents as housewives (52,5%). Baby blues is more experienced by mothers in young adulthood with multiparous status, secondary education level, and do not work outside the home. Suggestions for midwives are able to perform early detection of postpartum mothers who have the potential to experience baby blues.